Silver nanoclusters: synthesis, structures and photoluminescence. (17th June 2020) - Xie, Yun-Peng; Shen, Yang-Lin; Duan, Guang-Xiong; Han, Jun; Zhang, Lai-Ping; Lu, Xing
Abstract : This review summarizes recent advances in silver nanoclusters focusing on their controlled synthesis, crystal structures and photoluminescence. Abstract : Metal nanoclusters (NCs) consist of tens to hundreds of metal atoms with a diameter of <2 nm, and have attracted significant attention due to their unique molecule-like properties, such as well-defined molecular structures, explicit HOMO–LUMO transitions, quantized charge and strong luminescence emission. Various robust synthetic protocols have been successfully applied to the preparation of metal NCs. Among metal NCs, Au NCs stay at the frontline of this research, and more structural characteristics, particular optical, catalytic and electronic properties, and related technical applications of Au NCs have been discovered in recent years. By taking guidelines from Au NC research, Ag NCs have recently received increasing attention. In this review article, we first survey recent advances in developing efficient synthetic methods for Ag NCs, highlighting the underlying physical and chemical properties that make the delicate control of their sizes and surfaces possible. In the following section, we discuss recent advances in the structural determination of Ag NCs, such as Ag25 (2, 4-DMBT)18 (2, 4-DMBT: 2, 4-dimethylbenzenethiolate), Ag29 (1, 3-BDT)12 (1, 3-BDT: 1, 3-benzenedithiolate), and Ag44 (SR)30 (R = PhCO2 H2, PhF, PhF2 or PhCF3 ). Structural determination will help to gain deep insight into the structure–property relationships at the molecular level. In the last part, we highlight some examples of Ag NCs to demonstrate their photoluminescence properties, which offer potential applications as photodetectors and in sensing and bio-imaging. We give a brief outlook on the future development of Ag NCs from the viewpoint of synthesis and applications.